2013
DOI: 10.1159/000356073
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fetal Cells from the Maternal Circulation by Microarray Gene Expression Analysis - Could the Extravillous Trophoblasts Be a Target for Future Cell-Based Non-Invasive Prenatal Diagnosis?

Abstract: Introduction: Circulating fetal cells in maternal blood provide a tool for risk-free, non-invasive prenatal diagnosis. However, fetal cells in the maternal circulation are scarce, and to effectively isolate enough of them for reliable diagnostics, it is crucial to know which fetal cell type(s) should be targeted. Materials and Methods: Fetal cells were enriched from maternal blood by magnetic-activated cell sorting using the endothelial cell marker CD105 and identified by XY fluorescence in situ hybridization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 51 publications
1
84
0
Order By: Relevance
“…The few fetal cells required together with the use of automatic scanning for the detection of fetal cells [73] and SCs-WGA will help to overcome the problem of rarity of these cells in the maternal blood and make their use in NIPD much more easily achievable. Although this method is not yet completely mature due to the absence of a perfect antigen that can recognize 100% of fetal cells, relentless efforts continue and should lead to the development of this antigen in the near future [74,75]. However, this protocol will still be feasible with the available markers that recognize specific types of fetal cells as the fetal trophoblasts or normoblasts, but probably with a larger amount of maternal blood as there is no general agreement about their exact frequencies per ml of maternal blood.…”
Section: Discussionmentioning
confidence: 99%
“…The few fetal cells required together with the use of automatic scanning for the detection of fetal cells [73] and SCs-WGA will help to overcome the problem of rarity of these cells in the maternal blood and make their use in NIPD much more easily achievable. Although this method is not yet completely mature due to the absence of a perfect antigen that can recognize 100% of fetal cells, relentless efforts continue and should lead to the development of this antigen in the near future [74,75]. However, this protocol will still be feasible with the available markers that recognize specific types of fetal cells as the fetal trophoblasts or normoblasts, but probably with a larger amount of maternal blood as there is no general agreement about their exact frequencies per ml of maternal blood.…”
Section: Discussionmentioning
confidence: 99%
“…From these isolated fetal cells, we purified mRNA and generated a cDNA library, which we used to identify genes highly expressed in the fetal cells. Among the genes significantly overexpressed, more than half have important functions in the placenta and about 25% are expressed in extravillous and/or endovascular trophoblasts [6,7]. We therefore formulated the hypothesis that a major fraction of the fetal cells in maternal blood was of this type; thus, based on known expression patterns in these cells, we developed a method to enrich the endovascular trophoblasts in maternal blood based on CD105 and CD141 antibodies and final identification based on cytokeratin immunostaining [7].…”
Section: Methodsmentioning
confidence: 99%
“…We have established a method for isolating and identifying a population of fetal cells that is presumed to be an endovascular trophoblast (pEVT), a subgroup of the extravillous trophoblast from maternal blood [6,7]. If a sufficient number of pEVTs can be consistently isolated from maternal blood, then analysis of these cells may be developed into a NIPD of fetal chromosomal abnormalities, fetal infections, and placental dysfunction [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This analysis revealed that over half of the overexpressed genes in fetal cells were specific in extravillous trophoblasts (EVTs), indicating that this cell type could be a target in cbNIPD. In the placenta, some cytotrophoblasts from the column of the anchoring villi invade the maternal decidua [21]. Eventually we know that these invading trophoblasts line the spiral arteries, glands and veins and could be the source of fetal cells in maternal circulation [22].…”
Section: Trophoblastsmentioning
confidence: 99%